Hubungan Jenis Kelamin dan Gangguan Kognitif dengan Kejadian Depresi pada Lansia di Kelurahan Sambau Wilayah Kerja Puskesmas Sambau Kota Batam Tahun 2024 - Ninda Putri Nurjana; Nelli Roza; Resi Novia (Jurnal Ilmiah Kedokteran dan Kesehatan, 2026)
According to the WHO (2023), depression affects 3.8% of the global population, including 5.7% of adults over 60. In 2023, the SKI Report ranked depression in Riau Islands Province 13th (4,778 cases), and Batam City Health Office reported that mental emotional disorders were ranked 10th (0.06%). Depression is influenced by several factors, including gender and cognitive function. This study aimed to investigate the relationship between gender, cognitive impairment, and depression among the elderly in the Sambau working area of the Batam City Health Center. A cross-sectional research design was employed with 51 elderly participants selected through cluster sampling. Spearman's correlation statistical test was used to analyze the data. The results showed that gender had no significant relationship with depression (p-value = 0.338 > 0.05). However, cognitive impairment was significantly related to depression (p-value = 0.000 < 0.01). The study suggests that elderly individuals should actively participate in Posbindu activities for early detection of cognitive decline and depression, which can help prevent stress and memory loss.